Changes in the pattern of suicide attempters visiting the emergency room after COVID-19 pandemic: an observational cross sectional study - Ji-Hun Kang (BMC, 2021)
Abstract Background This study aimed to find out the change in the rate and pattern of suicide attempts during severe acute respiratory syndrome COVID-19 pandemic period. Methods This study was a retrospective analysis of data collected as a part of an emergency room-based post-suicide management program. The data were collected through interviews and from medical records of suicide attempts, maintained in the emergency room, from January 19 to October 31, 2020, during the “COVID-19 period,” and those who attempted suicide from January 19 to October 31, 2019 “pre-COVID-19 period.” We extracted educational background, marital status, occupation, presence of domestic partner, history of mental illness, alcohol consumption, history of previous suicide attempts; suicide attempt method and location (i.e., at home or a place other than home) at the time of attempt, and whether the attempt was a mass suicide. In addition, we compared patient severity between “COVID-19 period” and “pre-COVID-19 period” using the initial KTAS (South Korean triage and acuity scale) level, consciousness level, and systolic blood pressure. In 2012, KTAS was developed through the Ministry of Health and Welfare’s research project to establish triage system in South Korea. Results The analysis of the number of suicide attempts during “pre-COVID-19 period” and “ COVID-19 period” showed that the number of suicide attempts during “COVID-19 period” (n = 440) increased compared to the “pre-COVID-19 period” (n = 400). Moreover, the method of suicide attempts during “COVID-19 period” included overdose of drugs such as hypnotics, antipsychotics, and pesticides that were already possessed by the patient increased compared to the “pre-COVID-19 period” (P < 0.05). At the time of the visit to the emergency room, high KTAS level, low level of consciousness, and low systolic blood pressure, were observed, which were significantly different between “COVID-19 period” and “pre-COVID-19 period” (P < 0.05). Conclusion With the worldwide COVID-19 virus spread, suicide rate and suicide attempts at home have significantly increased. In addition, patient severity was higher in the “COVID-19 period” than that in the “pre-COVID-19 period.” The increasing suicide attempt rate should be controlled by cooperation between the emergency room and regional organizations.